Simultaneous determination of ezetimibe and simvastatin in rat plasma by stable-isotope dilution LC-ESIâMS/MS and its application to a pharmacokinetic study - Sireesha R. Karanam; Prakash Katakam; Babu R. Chandu; Nagiat T. Hwisa; Shanta K. Adiki (Elsevier, 2014)
A simple, sensitive and specific liquid chromatographyâtandem mass spectrometry method was developed for simultaneous quantification of ezetimibe and simvastatin in rat plasma. The deuterium isotopes: ezetimibe d4 and simvastatin d6 were used as internal standards for ezetimibe and simvastatin, respectively. MS/MS detection involved a switch of electron spray ionization mode from negative to positive at retention time 3.01Â min. Samples were extracted from plasma by liquidâliquid extraction using tertiary butyl methyl ether. Chromatographic separation was achieved with Agilent Eclipse XBD-C18 column using mobile phase that consisted of a mixture of ammonium acetate (pH4.5; 10Â mM)âacetonitrile (25:75 v/v). The method was linear and validated over the concentration range of 0.2â40.0Â ng/mL for simvastatin and 0.05â15.0Â ng/mL for ezetimibe. The transitions selected were m/z 408.3â271.1 and m/z 412.0â275.10 for ezetimibe and ezetimibe d4, and m/z 419.30â285.20 and m/z 425.40â199.20 for simvastatin and simvastatin d6. Intra- and inter-batch precisions for ezetimibe were 1.6â14.8% and 2.1â13.4%; and for simvastatin 0.94â9.56% and 0.79â12%, respectively. The proposed method was sensitive, selective, precise and accurate for the quantification of ezetimibe and simvastatin simultaneously in rat plasma. The method was successfully applied to a pharmacokinetic study by oral co-administration of ezetimibe and simvastatin in SD rats. Keywords: Ezetimibe, Simvastatin, Pharmacokinetics, Rat plasma, LC-ESIâMS/MS